Knowledge, attitude and practices about diabetes mellitus and its complications in T2DM patients attending the UHC in Mumbai - Kazi, Rufiat Nasiruddin; Bote, Mangala M.; Raikar, Kedar J. (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes Mellitus has become a major public health problem in India and also the major cause of disability through complications such as blindness, renal failure, lower limb gangrene etc. People suffering from Diabetes related complications are many times unaware about the measures to curb the onset of the complications. The aim of the study was to assess knowledge, attitude and practices about diabetes and its complications in the diabetic patients Methods: This was a cross sectional descriptive study conducted at an Urban Health Centre attached to the parent medical college in Mumbai. The knowledge, attitude and practices of the 116 participants who were registered at the non-communicable disease (NCD) OPD were assessed via a pre-designed, pre-tested interviewer administered questionnaire. Statistical analysis used: SPSS version 20. Results: Majority belonged the age groups of 40-60 years (69%), 63.8% were women, 91.4% were married and 44.4% were illiterate. 13.8% of the respondents had correct knowledge about the causes of diabetes and 62.9% could correctly identify the symptoms of diabetes. Knowledge regarding the complications in diabetics was found to be quite low with only 52.6% correctly identifying one or more complications. The most commonly known complication was neuropathy (83.6%) followed by nephropathy (57.3%). The attitude of the patients with respect to screening of complications was found to be poor and the same reflected in their practices Conclusions: There is a lack of understanding of the basics of the disease, its prevention as well as prevention of complications in those suffering from the disease.